2011
DOI: 10.1037/a0024194
|View full text |Cite
|
Sign up to set email alerts
|

In search of on-line locality effects in sentence comprehension.

Abstract: Many comprehension theories assert that increasing the distance between elements participating in a linguistic relation (e.g., a verb and a noun phrase argument) increases the difficulty of establishing that relation during on-line comprehension. Such locality effects are expected to increase reading times and are thought to reveal properties and limitations of the short-term memory system that supports comprehension. Despite their theoretical importance and putative ubiquity, however, evidence for on-line loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
2
5

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(80 citation statements)
references
References 53 publications
1
72
2
5
Order By: Relevance
“…For example, Grodner and Gibson (2005) and Bartek, Lewis, Vasishth, and Smith (2011) present evidence that in English argument-verb dependencies, increasing the distance between the verb and the argument leads to slower reading times. A similar pattern is observed in argument-verb dependencies in Russian RCs , and this has been replicated in Hungarian (Kovács & Vasishth, 2013).…”
Section: Discussionmentioning
confidence: 97%
“…For example, Grodner and Gibson (2005) and Bartek, Lewis, Vasishth, and Smith (2011) present evidence that in English argument-verb dependencies, increasing the distance between the verb and the argument leads to slower reading times. A similar pattern is observed in argument-verb dependencies in Russian RCs , and this has been replicated in Hungarian (Kovács & Vasishth, 2013).…”
Section: Discussionmentioning
confidence: 97%
“…To preview our conclusion, the results of our investigation support the main predictions of the Local Search hypothesis. We argue that the Local Search hypothesis offers important insight into a widely-observed preference for local dependencies over distant dependencies in sentence comprehension (Kimball, 1973; Hawkins, 1994; Gibson, 1998; Bartek et al, 2011; a . o .).…”
Section: Introductionmentioning
confidence: 91%
“…It is widely observed that local syntactic dependencies are easier to process or, in cases of ambiguity, preferred over longer syntactic dependencies (Kimball, 1973; Frazier, 1978; Just and Carpenter, 1992; Hawkins, 1994; Gibson, 1998; Lewis and Vasishth, 2005; Lewis et al, 2006; Bartek et al, 2011; inter alia ). Because cue-based, direct access mechanisms do not need to execute a serial search of a parse to retrieve a syntactic dependent or a pronominal antecedent, locality effects cannot emerge as a property of the access mechanism without making further assumptions.…”
Section: Introductionmentioning
confidence: 99%
“…In Experiment 1, this trend emerged starkly in the most difficult conditions, according to independent reading time evidence (Bartek et al 2011). In the easier conditions, where there was no embedding of the subject NP, there was essentially no variation ascribable due to individual differences on the reading span task (see Figure 2).…”
Section: Individual Differences and Acceptability Judgmentsmentioning
confidence: 99%